2010
DOI: 10.1371/journal.pone.0015133
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C: A Candidate Biomarker for Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurologic disease characterized by progressive motor neuron degeneration. Clinical disease management is hindered by both a lengthy diagnostic process and the absence of effective treatments. Reliable panels of diagnostic, surrogate, and prognostic biomarkers are needed to accelerate disease diagnosis and expedite drug development. The cysteine protease inhibitor cystatin C has recently gained interest as a candidate diagnostic biomarker for ALS, but further stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 30 publications
3
73
0
1
Order By: Relevance
“…However, only the trend in the slow progressors was significant. In contrast to these findings, plasma levels of cystatin C were significantly higher in patients with ALS as compared with healthy controls [105]. While protein levels can provide insight into the physiology and pathology, protein levels do not necessarily correlate with enzymatic activity, highlighting a significant limitation to the studies performed to date.…”
Section: Cystatin Cmentioning
confidence: 67%
See 3 more Smart Citations
“…However, only the trend in the slow progressors was significant. In contrast to these findings, plasma levels of cystatin C were significantly higher in patients with ALS as compared with healthy controls [105]. While protein levels can provide insight into the physiology and pathology, protein levels do not necessarily correlate with enzymatic activity, highlighting a significant limitation to the studies performed to date.…”
Section: Cystatin Cmentioning
confidence: 67%
“…Levels of cystatin C positively correlated with survival time for patients with limb onset but did not correlate with the disease duration [98]. A longitudinal study was also performed on CSF and plasma over a 1 to 2-year time period [105]. In this study, analyses of cystatin C levels in the CSF showed that fast and slow progressors exhibited trends towards decreased and increased levels over time, respectively.…”
Section: Cystatin Cmentioning
confidence: 77%
See 2 more Smart Citations
“…In addition to these readily obtained laboratory tests, a variety of disease-specific biomarkers have been sought including neurofilament heavy subunit, both in serum and cerebrospinal fluid (CSF) [88,89], and CSF cystatin C [90,91]. Cystatin C levels have also been found to correlate with the rate of disease progression and are predictive of survival [90].…”
Section: Serum and Cerebrospinal Fluid Biomarkersmentioning
confidence: 99%